2022
DOI: 10.1038/s41590-022-01170-w
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1–PD-1 interactions limit effector regulatory T cell populations at homeostasis and during infection

Abstract: Phenotypic and transcriptional profiling of Treg cells at homeostasis reveals that TCR activation promotes Treg cells with an effector phenotype (eTreg) characterized by the production of IL-10 and expression of the inhibitory receptor PD-1. At homeostasis, blockade of the PD-1 pathway results in enhanced eTreg cell activity while during infection with T. gondii early IFN-γ upregulates myeloid cell expression of PD-L1 associated with reduced Treg cell populations. In infected mice, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 62 publications
5
56
0
Order By: Relevance
“…japonicum infection, although the number of eggs was reduced significantly in PD-1-deficient mice and the granuloma size per egg concordantly increased. It is worth mentioning that in an infection model using Toxoplasma gondii , blockade of PD-L1, germline deletion of PD-1, or PD-1 deficiency in Tregs resulted in reduced pathogen-specific CD4 + T cell responses during infection [ 16 ]. Such discrepancies between different infection models suggest that the consequence of PD-1 deficiency is pathogen-dependent, revealing the complexity of modulating T cell responses via PD-1 to treat schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…japonicum infection, although the number of eggs was reduced significantly in PD-1-deficient mice and the granuloma size per egg concordantly increased. It is worth mentioning that in an infection model using Toxoplasma gondii , blockade of PD-L1, germline deletion of PD-1, or PD-1 deficiency in Tregs resulted in reduced pathogen-specific CD4 + T cell responses during infection [ 16 ]. Such discrepancies between different infection models suggest that the consequence of PD-1 deficiency is pathogen-dependent, revealing the complexity of modulating T cell responses via PD-1 to treat schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are in line with findings from cancer immunotherapies in which PD-1 blockade results in increased Treg suppression [ 14 ], which needs further verification as some studies reported opposite results that PD-1 blockade could help overcome Treg suppression [ 15 ]. Surprisingly another recent study showed that decreased antigen specific T cell response in Toxoplasma gondii infected mice which had germline deletion of PD-1 or Treg specific ablation of PD-1, was associated with increased parasite burden [ 16 ]. In a previous study, PD-1 blockade in mice were found to exacerbate liver pathology and enhance Th2 differentiation [ 17 ], however the consequence of PD-1 inhibition for pathogens or the T cell response in the liver were not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 expression is induced in T cells by persistent antigenic stimulation, and thus is related to T-cell "exhaustion" in chronic infections and cancer 7 8 . Blockade of the PD-1 axis by either anti-PD-1 or anti-PD-L1 can inhibit PD-1 binding to PD-L1 and thereby abrogate inhibitory PD-1 signalling 9 , in addition, the PD-1 signalling pathway may inhibit Treg activities 10,11 . Thus, simultaneous blockade of CTLA-4 and PD-1 has been shown to induce robust antitumour T cell responses 12 , through expanding activated effector CD8 + T cells 13 14 , and a reduction in Treg-mediated immune-suppression 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there need to be mechanisms to balance T reg cell activities such as IL-2 availability as a mechanism involved in modulation of the T reg cell pool 25,26 . In addition, there is evidence that the inhibitory receptors PD-1 27,28 and CTLA-4 21 restrict T reg cell activities in the setting of cancer, autoimmunity and infection 21,22,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ability of the extracellular domain of CTLA-4 to sequester CD80/86 provides an additional trans mechanism to limit accessory cell function required for optimal effector T cell activities 32 . A subset of T reg cells also express these receptors 22,28 , and several reports have highlighted that effector (eT reg ) cells express the highest levels of PD-1 and CTLA-4 27,28 . It appears that eT reg cells receive continuous TCR signals, but constitutive signals through PD-1 constrain the size of the eT reg cell pool 27,28 .…”
Section: Introductionmentioning
confidence: 99%